(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Coordination compounds of intermediate metals are increasingly used in various fields of science and technology. The study of complexing with new classes of organic ligands opens up broad prospects for their application in metallurgy, chemical industry, medicine and agriculture. The rapid development of coordination chemistry is directly related to the study of the role of metal complexes in vital processes. The study of the mechanism of action of physiologically active substances on biological membranes, enzymes, etc. is one of the current issues. Although coordination compounds of intermediate metals with 2- [phenylmethyl] -1H-benzimidazole derivatives have been considered in many studies, at the beginning of our study there were no data on mixed-ligand coordination compounds of silver containing benzimidazole derivatives. Around the central atom, benzimidazole as the main ligand and diethyldithiocarbamate as the mixed ligand complex compounds have not been synthesized and the reasons for the competitive coordination of the ligands have not been shown.